The effect of long-term consumption of calabash chalk on peptic ulcer scores in albino Wistar rats (Nigerian Journal of Physiological Sciences, 2025)
This study aimed to demonstrate the effects of long-term consumption of calabash chalk on ulcer scores in Albino Wistar rats. Fifty (50) male adult Albino Wistar rats weighing between 160g - 180g were used for the experiment. The rats were randomly divided into ten (10) groups of 5 rats each consisting of five (5) control and five (5) test rats. Group 1 was the control group and was administered 1ml of distilled water daily while group 2 was the test group and was administered 1ml of calabash chalk suspension orally daily. They were allowed food and water ad libitum. The experiment lasted for 28 days, thereafter, basal gastric acid secretion, gastric pepsin secretion, gastric pH, gastric mucous output, and gastric ulcer scores were measured. The mean basal gastric acid secretion for the control and the test group was 0.58 ± 0.22 and 0.61 ± 0.37uMol/10min respectively. The result showed that the mean basal gastric acid secretion was not significantly higher in the test group when compared with the control group. The mean gastric pepsin secretion for the control and the test group was 0.46 ± 0.02 and 0.57 ± 0.02mg/100ml respectively. The results showed that the mean gastric pepsin secretion in the test group was significantly higher (P